PELAFALAN BAHASA INGGRIS OLEH PEGAWAI CUSTOMER SERVICE BANDARA INTERNASIONAL ADI SOEMARMO SURAKARTA - Fajri, Amalia Ramadhani; Hadiningrum, Indriyati (Jurnal Vokasia, 2021)
This article is written based on a job training done at the international airport of Adi Soemarmo. The focus is to figure out the English pronunciation of the customer service staff when they help tourists find information. The data is collected by observation, interview, and literary study. The result shows that, in general, foreign tourists are happy when the customer service staff can communicate using the English language. However, the staff still find problems especially when tourists cannot speak English or when seeing unfriendly tourists. Thus, it is suggested that the customer service staff keep improving their English skills and behave in a pleasant way to tourists.